2009
DOI: 10.1021/ac901753c
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Hue Parameter of the Hue, Saturation, Value Color Space As a Quantitative Analytical Parameter for Bitonal Optical Sensors

Abstract: The hue or H component of the hue, saturation, value (HSV) color space has been studied as a quantitative analytical parameter for bitonal optical sensors. The robust nature of this parameter provides superior precision for the measurement of sensors which change colors with the speciation of some indicator molecule. This parameter has been compared to red, green, blue (RGB) intensity and RGB absorbance along with differences and ratios of both intensity and absorbance and has been demonstrated to be 2 to 3 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(162 citation statements)
references
References 45 publications
(97 reference statements)
5
148
1
Order By: Relevance
“…The used scanner has a 6400 x 3200 dpi resolution and a maximum optical density of 4.2 and 24 to 48 bits of colour. The H parameter is calculated from the scanned image using the software Matlab r2007b (The MathWorks, Inc, Natick, MA, USA) [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The used scanner has a 6400 x 3200 dpi resolution and a maximum optical density of 4.2 and 24 to 48 bits of colour. The H parameter is calculated from the scanned image using the software Matlab r2007b (The MathWorks, Inc, Natick, MA, USA) [7].…”
Section: Resultsmentioning
confidence: 99%
“…However, in this work, we used the HSV colour space, whose main characteristic is that it represents the useful information of the colour in one single parameter, the coordinate H (hue). Previous studies from our group have shown that the use of the H coordinate in bitonal sensors that produce a change in colour by reaction yields a substantial improvement in resolution and repeatability [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, many color spaces are available for standardizing color such as RGB -red, green, and blue; CMYK -cyan, magenta, yellow, and black; CIE L à a à b; and HSV -hue, saturation, and value (see the review of Cheng et al [79] for comprehensive mathematical derivation for all of them). The later color space (HSV) was particularly evaluated in quantitative analytical processing by Cantrell et al [80] and they found that the H-parameter was the most robust for quantitative determination when color change was involved in the chemical analysis.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Colors are present or represented in visual experiences. Color spaces specify colors from the three primary colors; red, green, and, blue [16]. There are many color spaces to quantify color and they can be classified into four groups that are connected by different types of transformations; linear light tristimulus, this color space was created by the International Commission on Illumination (CIE) (CIE XYZ, and CIE RGB), xy chromaticity (CIE xyY), perceptually uniform, and hue oriented (HLS, HSV) [16].…”
Section: Hue Saturation and Valuementioning
confidence: 99%
“…Color spaces specify colors from the three primary colors; red, green, and, blue [16]. There are many color spaces to quantify color and they can be classified into four groups that are connected by different types of transformations; linear light tristimulus, this color space was created by the International Commission on Illumination (CIE) (CIE XYZ, and CIE RGB), xy chromaticity (CIE xyY), perceptually uniform, and hue oriented (HLS, HSV) [16]. The red, green, blue (RGB) color space is used by scanners and digital cameras; it is an additive representation as all of the colors can be represented as a combination of red, green and blue when these three colors are combined [17].…”
Section: Hue Saturation and Valuementioning
confidence: 99%